Comparing invasive hemodynamic responses in adenosine hyperemia versus physical exercise stress in chronic coronary syndromes. (1st November 2021) - Cook, Christopher M.; Howard, James P.; Ahmad, Yousif; Shun-Shin, Matthew J.; Sethi, Amarjit; Clesham, Gerald J.; Tang, Kare H.; Nijjer, Sukhjinder S.; Kelly, Paul A.; Davies, John R.; Malik, Iqbal S.; Kaprielian, Raffi; et al.
Abstract: Objectives: Adenosine hyperemia is an integral component of the physiological assessment of obstructive coronary artery disease in patients with chronic coronary syndrome (CCS). The aim of this study was to compare systemic, coronary and microcirculatory hemodynamics between intravenous (IV) adenosine hyperemia versus physical exercise stress in patients with CCS and coronary stenosis. Methods: Twenty-three patients (mean age, 60.6 ± 8.1 years) with CCS and single-vessel coronary stenosis underwent cardiac catheterization. Continuous trans-stenotic coronary pressure-flow measurements were performed during: i) IV adenosine hyperemia, and ii) physical exercise using a catheter-table-mounted supine ergometer. Systemic, coronary and microcirculatory hemodynamic responses were compared between IV adenosine and exercise stimuli. Results: Mean stenosis diameter was 74.6% ± 10.4. Median (interquartile range) FFR was 0.54 (0.44–0.72). At adenosine hyperemia versus exercise stress, mean aortic pressure (Pa, 91 ± 16 mmHg vs 99 ± 15 mmHg, p  < 0.0001), distal coronary pressure (Pd, 58 ± 21 mmHg vs 69 ± 24 mmHg, p  < 0.0001), trans-stenotic pressure ratio (Pd/Pa, 0.63 ± 0.18 vs 0.69 ± 0.19, p  < 0.0001), microvascular resistance (MR, 2.9 ± 2.2 mmHg.cm −1 .sec −1 vs 4.2 ± 1.7 mmHg.cm −1 .sec −1, p  = 0.001), heart rate (HR, 80 ± 15 bpm vs 85 ± 21 bpm, p  = 0.02) and rate-pressure product (RPP, 7522 ± 2335 vs 9077 ± 3200, p  = 0.0001) were all lower. Conversely, coronary flow velocity (APV, 23.7 ± 9.5 cm/s vs 18.5 ± 6.8 cm/s, p  = 0.02) was higher. Additionally, temporal changes in Pa, Pd, Pd/Pa, MR, HR, RPP and APV during IV adenosine hyperemia versus exercise were all significantly different ( p  < 0.05 for all). Conclusions: In patients with CCS and coronary stenosis, invasive hemodynamic responses differed markedly between IV adenosine hyperemia versus physical exercise stress. These differences were observed across systemic, coronary and microcirculatory hemodynamics. Highlights: What is already known about this subject?: Adenosine hyperemia leads to vasodilatation of the coronary microcirculation and stabilization of microvascular resistance. This in turn permits the use of hyperemic coronary pressure ratios to quantify the flow-limiting potential of a coronary stenosis (i.e. the Fractional Flow Reserve). What does this study add?: In patients with chronic coronary syndrome (CCS) and coronary stenosis, invasive hemodynamic responses differed markedly between adenosine hyperemia versus physical exercise stress. These differences were observed across systemic, coronary and microcirculatory hemodynamics. How might this impact on clinical practice?: Adenosine hyperemia is a validated and integral component of functional myocardial ischemia assessment, both invasively and non-invasively. However, the findings of the present study (as well as previous studies) remind the clinician that the physiological and hemodynamic responses to adenosine hyperemia cannot be considered as directly comparable to those of physical exercise.